2021
DOI: 10.1002/ppul.25613
|View full text |Cite
|
Sign up to set email alerts
|

The indispensable role of pharmacy services and medication therapy management in cystic fibrosis

Abstract: Care for people with cystic fibrosis (PWCF) is highly complex and requires a multidisciplinary approach where the pharmacist plays a vital role. The purpose of this manuscript is to serve as a guideline for pharmacists and pharmacy technicians who provide care for PWCF by providing background and current recommendations for the use of cystic fibrosis (CF)-specific medications in both the acute and ambulatory care settings. The article explores current literature surrounding the role of pharmacists and pharmacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 90 publications
0
17
0
Order By: Relevance
“…Haywood and Goralski which found that 59% (51/92) of PwCF at their CF center did not have an identified primary care physician (PCP) or had the CF provider listed as the PCP. 18 Over the years, pharmacists and pharmacy technicians have been expanding their involvement as part of CF care teams and are now recognized as recommended or dedicated members of CF care teams in Europe, the United Kingdom (UK), Australia, and the U.S. [3][4][5][6][7][8] With this expansion of involvement, integrated pharmacy teams (pharmacists and pharmacy technicians) have established many roles as part of those CF care teams. 6,7 One role that has not been recognized previously is administration of immunizations by pharmacy team members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haywood and Goralski which found that 59% (51/92) of PwCF at their CF center did not have an identified primary care physician (PCP) or had the CF provider listed as the PCP. 18 Over the years, pharmacists and pharmacy technicians have been expanding their involvement as part of CF care teams and are now recognized as recommended or dedicated members of CF care teams in Europe, the United Kingdom (UK), Australia, and the U.S. [3][4][5][6][7][8] With this expansion of involvement, integrated pharmacy teams (pharmacists and pharmacy technicians) have established many roles as part of those CF care teams. 6,7 One role that has not been recognized previously is administration of immunizations by pharmacy team members.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published literature has highlighted the roles of the integrated pharmacy team in the care of PwCF and the established care process model of the integrated pharmacy team 6,7 . One role that was not specifically addressed was the administration of routine and recommended immunizations to PwCF.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2022 Remaining Barriers to Normalcy in Cystic Fibrosis VII supplemental edition of this Journal, Grant and colleagues presented a comprehensive review of the role that pharmacists and pharmacy technicians play in providing care to people with cystic fibrosis (CF). 1 Pharmacists are recommended team members by the Cystic Fibrosis Foundation for the care of people with CF, and specific duties of pharmacists are outlined in several international CF care center guidelines. Published literature by Zobell et al 2 and Autry and Kuhn 3 demonstrated improvement in patients with CF not only in medication adherence, but also in body weight, body mass index, and decreasing hospitalizations for patients with an integrated pharmacy team.…”
Section: To the Editormentioning
confidence: 99%
“…In the 2022 Remaining Barriers to Normalcy in Cystic Fibrosis VII supplemental edition of this Journal, Grant and colleagues presented a comprehensive review of the role that pharmacists and pharmacy technicians play in providing care to people with cystic fibrosis (CF) 1 . Pharmacists are recommended team members by the Cystic Fibrosis Foundation for the care of people with CF, and specific duties of pharmacists are outlined in several international CF care center guidelines.…”
Section: To the Editormentioning
confidence: 99%
“…Involvement of a pharmacy clinician is important, given the complexity and medication toxicity profiles utilized in patients with DLD. There is precedence of the importance of clinical pharmacist involvement in the care of CF, 19 and their involvement is likely to benefit other multidisciplinary clinics such as a RLD program. Although dedicated support may be challenging given the rare nature of these diseases and patients, consideration should be given to including as part of the team a pharmacist who has experience with pulmonary and/or immunosuppressant agents.…”
Section: Defining the “Who”: What Colleagues Will Populate Your “Vill...mentioning
confidence: 99%